Strategi Implementasi Program Peningkatan Partisipasi Pembangunan Kecamatan (P3K) di Kecamatan Nyalindung Kabupaten Sukabumi - Rio Muhammad Fajar; Endang Wirjatmi; Hendrikus T Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
Program Peningkatan Partisipasi Pembangunan Kecamatan (P3K) is a form of implementation of policies to increase community participation in development in Sukabumi Regency with a regional development framework as a strategic foundation for the realization of the acceleration of region-based poverty reduction through increasing community participation and capacity. This research was conducted using qualitative methods with an inductive approach so that it can produce a general conclusion drawn from empirical fact-finding at the research location. So far, the implementation of activities in the P3K Program in Nyalindung district has been in accordance with the operational guidelines. However, in the process, there are still various obstacles, including the absence of a measuring tool for the success of the program, the capacity of human resources is very limited and the dependence on the budget from the government is very high. Based on the results of the SWOT analysis, P3K program implementation strategy in Nyalindung district needs to be made to measure the success of the program in the form of a Key Performance Indicator (KPI) and collaboration with various parties through the Penta Helix model. Therefore, researchers provide suggestions for drafting revisions to operational technical guidelines by adding rules regarding management and monitoring mechanisms for development results. In addition, in order to increase the capacity of program actors, it is necessary to conduct training for all stakeholders involved in order to equalize perceptions of P3K Program.